2009
DOI: 10.1111/j.1834-7819.2009.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of bovine derived xenograft with and without a bioabsorbable collagen membrane in the treatment of mandibular Class II furcation defects

Abstract: Background: The aim of this study was to compare the clinical outcomes of applying Bio-OssÒ, an anorganic bovine bone xenograft (control group) to the combined use of Bio-OssÒ and Bio-GideÒ (a bioabsorbable collagen membrane) (test group) in human mandibular Class II furcation defects. Methods: A total of 18 furcations (8 tests and 10 controls) in 14 patients suffering from chronic periodontitis were treated in this randomized clinical trial. Open vertical and horizontal furcation depths (OVFD and OHFD), verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 32 publications
(42 reference statements)
3
16
0
5
Order By: Relevance
“…The probing depth in this study was decreased with a ratio of 50%. Such significant pocket depth reduction is important, because this parameter serves as a diagnostic test with high sensitivity and specificity [14][15][16]. Aukhil et al also found that placement of physical barriers between the root surface and flaps may be beneficial in facilitating coronal migration of progenitor cells from the periodontal ligament [1].…”
Section: Resultsmentioning
confidence: 97%
“…The probing depth in this study was decreased with a ratio of 50%. Such significant pocket depth reduction is important, because this parameter serves as a diagnostic test with high sensitivity and specificity [14][15][16]. Aukhil et al also found that placement of physical barriers between the root surface and flaps may be beneficial in facilitating coronal migration of progenitor cells from the periodontal ligament [1].…”
Section: Resultsmentioning
confidence: 97%
“…Dessa forma, focando nesses defeitos de difícil regeneração, foi proposto o seu preenchimento com enxertos, autógeno ou alógeno, e biomateriais com base nos princípios da regeneração óssea (MARDAS et al, 2003;TAHERI et al, 2009). Os resultados são variáveis dependendo muito da morfologia do defeito periodontal (MARDAS et al, 2003;DUARTE et al, 2006;TAHERI et al, 2009;TSIOMIS et al, 2010).…”
Section: Regeneração Periodontal Na Odontologia Veterináriaunclassified
“…Os resultados são variáveis dependendo muito da morfologia do defeito periodontal (MARDAS et al, 2003;DUARTE et al, 2006;TAHERI et al, 2009;TSIOMIS et al, 2010). O preenchimento de defeitos de furca classe II com enxertos ou biomateriais não contribuiu para uma maior quantidade de tecidos regenerados, sendo frequente a ocorrência de anquilose e reabsorção da raiz dentária.…”
Section: Regeneração Periodontal Na Odontologia Veterináriaunclassified
See 1 more Smart Citation
“…Além de servir de matriz para a regeneração óssea ele também oferece resistência dimensional, evitando o colapso da membrana para o interior do defeito. Nos defeitos periodontais favoráveis, ou seja, aqueles que possuem diversas paredes ósseas, o OBI tem apresentado resultados previsíveis (TAHERI et al, 2009;STAVROPOULOS;KARRING, 2010;BALDINI;DE SANCTIS;FERRARI, 2011).…”
Section: Enxerto óSseo Bovino Inorgânicounclassified